2004
DOI: 10.1186/1476-7120-2-11
|View full text |Cite
|
Sign up to set email alerts
|

Stress echocardiography in heart failure

Abstract: Echocardiography has the ability to noninvasively explore hemodynamic variables during pharmacologic or exercise stress test in patients with heart failure. In this review, we detail some important potential applications of stress echocardiography in patients with heart failure. In patients with coronary artery disease and chronic LV dysfunction, dobutamine stress echocardiography is able to distinguish between viable and fibrotic tissue to make adequate clinical decisions. Exercise testing, in combination wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 55 publications
0
36
0
3
Order By: Relevance
“…When a physiological (exercise) stress echo is scheduled, interest is focused on wall motion segmental contraction abnormality to diagnose ischemic response to stress [9] and on LVEF to assess contractile reserve: the critical level to define the presence of contractile reserve is generally defined as an increase of at least 5% (in absolute terms) in the global LVEF [27]. However, ejection fraction is a very gross index of left ventricular performance.…”
Section: Pvr Vs Lvef Contractile Reserve Evaluationmentioning
confidence: 99%
“…When a physiological (exercise) stress echo is scheduled, interest is focused on wall motion segmental contraction abnormality to diagnose ischemic response to stress [9] and on LVEF to assess contractile reserve: the critical level to define the presence of contractile reserve is generally defined as an increase of at least 5% (in absolute terms) in the global LVEF [27]. However, ejection fraction is a very gross index of left ventricular performance.…”
Section: Pvr Vs Lvef Contractile Reserve Evaluationmentioning
confidence: 99%
“…37,[41][42][43][44] Exercise testing, in combination with echocardiographic monitoring, may be an attractive and practical method of obtaining accurate information that can aid in the assessment of contractile reserve and prognosis. 38) Observations from previous studies have shown that the capacity for exercise in patients with advanced HF may in fact be more closely related to RV rather than LV performance. 9) RV dysfunction predicts an impaired contractile reserve and decreased survival in patients with both moderate and advanced HF.…”
Section: )mentioning
confidence: 99%
“…9,[36][37][38][39][40] These conventional parameters during exercise could show a reserve of cardiac function, activity, and quality of life in patients with HF, but those at rest could not. We need to determine the responses to therapy that lead to a good prognosis in patients with DCM.…”
Section: )mentioning
confidence: 99%
“…Išemine KMP sergantiems pacientams, kuriems medikamentinis ŠN gydymas neveiksmingas, atlikta KS rekonstrukcinė operacija žymiai sumažina simptomus, o KS galinis diastolinis tūrio sumažinimas iki <150 ml po operacijos leidžia prognozuoti gerus trumpalaikius rezultatus (15). Jeigu KS galinis sistolinis tūris didelis (140 ml) dėl KS remodeliavimosi, KS funkcijos pagerėjimo tikimybė yra maža (21). Po MI susiformavusi KS aneurizma yra nepriklausomas blogos prognozės požymis.…”
Section: Chirurginis Gydymas Taikomas Tais Atvejais Kai Yra Vidutiniunclassified